The Cultivation Of The Religious Values As Character Forming Students - Nur Aisyah; Suratno (STAI Miftahul Ula Nganjuk, 2019)
Character education in schools aimed at improving the quality of the implementation and results of school education towards achieving the formation of character and noble character of learners as a whole, integrated, balanced and appropriate competency standards. Character education is applied in the implementation of learning by using a contextual approach for students to connect or associate materials studied to real life. This study aimed to describe the implementation of character education, the curriculum used, and the results achieved in shaping the character of students. The research was carried out by a naturalistic qualitative approach, and its subjects were the Elementary School’s principal, vice principal, teachers/homeroom teachers and students and the students’ parents. The data were collected through observation and interviewing and document analysis. The validity of data was used the source, method, and theory triangulation, the prolongation of observation, continous observation, sufficient reference, checking partners through discussion, and member check. The data analysis included the data reduction, data display and conclusion. The result of the research are: (1) character education planning is done by integrating the religious values ​​are matched with the standards of competence and basic competence, suitability with the material, and are translated into a learning device. Character values ​​developed or implemented through habituation and exemplary school culture, (2) the implementation of character education is done in learning is divided into three sections, the first integrated into the subjects, both in local content, and the third through the self-development of habituation, exemplary, and extracurricular. Character education in extracurricular activities carried out by entering the value of the main characters in each activity option. Barriers to implementation of the characteristics of students, families, and communities. Facilities and support facilities play an important role in the integration of the value of the character, (3) character education evaluation process carried out during the learning process and when students interact outside the classroom which in turn reported to students parents.